INSTAGRAM @TAULEBIH.ID CONTENT MANAGEMENT STRATEGIES AS ISLAMIC SEXUALITY EDUCATION MEDIA FOR YOUNG GENERATION - Ghalda Nauli Siregar; Mochammad Fauzul Haq; Siti Fatonah (INJECT (Interdisciplinary Journal of Communication), 2023)
This study aims to determine the content management strategy of @taulebih.id as a medium for Islamic sexuality education to the younger generation. Descriptive qualitative methods in this research obtained the results of the content management strategy used by @taulebih.id prioritizing trends, content messages, and visuals. The interaction builder with the audience @taulebih.id does not use influencers to promote the account but invites expert speakers. Content management of many human resources is a supporting factor for producing content.